Development of Flipbook-Based PAI Modules on the Material of Belief in Allah and His Messenger for Grade IV in Elementary Schools - Lutfiatul Azkia; Maemunah Sa’diyah; Abas Mansur Tamam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Problems of learning activities in educational institutions are influenced by several factors including the use of teaching materials, conventional learning methods, and low student interest in learning. The learning process that feels boring makes it difficult for students to receive the material presented, because the learning only focuses on information from one side (Teacher Center). In addition, the world of education today has the development of information and communication technology that has a very large influence, including on digital learning sources that are easy to access. Therefore, the learning system becomes easier with the existence of digital-based learning modules that can be accessed anywhere and anytime and become teaching materials in explaining learning materials. This study aims to determine the feasibility of developing a flipbook-based PAI module on the material of believing in Allah and His Messenger for grade IV in elementary schools. This study is a type of Research and Development (R&D) research and development with the ADDIE model consisting of five stages, namely Analyze, Design, Development, Implementation, and Evaluation. The research data sources consist of the results of observations and interviews and questionnaires with experts, principals, Islamic Religious Education teachers and students. Meanwhile, statistical data were obtained from the results of questionnaires from experts, practitioners and students analyzed using a Likert scale. The results of this study obtained a flipbook-based PAI module on the material of faith in Allah and His Messenger for grade IV with decent and very good results, based on suggestions/input and assessments from experts and practitioners. Thus, the flipbook-based PAI module can be used as teaching materials for teachers and students in the learning process at school.